Lasers and intense pulsed light (IPL) association with cancerous lesions - Ash, Caerwyn (Lasers Med Sci, 2017)
The development and use of light and lasers for medical and cosmetic procedures has increased exponentially over the past decade. This review article focuses on the incidence of reported cases of skin cancer post laser or IPL treatment. The existing evidence base of over 25 years of laser and IPL use to date has not raised any concerns regarding its long-term safety with only a few anecdotal cases of melanoma post treatment over two decades of use; therefore, there is no evidence to suggest that there is a credible cancer risk. Although laser and IPL technology has not been known to cause skin cancer, this does not mean that laser and IPL therapies are without long-term risks. Light therapies and lasers to treat existing lesions and CO(2) laser resurfacing can be a preventative measure against BCC and SCC tumour formation by removing photo-damaged keratinocytes and encouraged re-epithelisation from stem cells located deeper in the epidermis. A review of the relevant literature has been performed to address the issue of long-term IPL safety, focussing on DNA damage, oxidative stress induction and the impact of adverse events.